A Literature Review On Adolescent Mental Health Management: A Literature Review On Adolescent Mental Health Management - netty, Netty Purba; Erika Fariningsih; Devi Khiran Novelina, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Adolescent health and well-being during adolescence and adulthood depend on preventing adversity, fostering socioemotional learning and psychological well-being, and guaranteeing access to mental health care. The formative years of adolescence are critical for the development of social and emotional skills necessary for mental health. Adoles Mental health is impacted by several variables. The possible impact on adolescents' mental health increases with the number of risk factors they are exposed to. Adversity, peer pressure, and identity exploration are some of the factors that can lead to stress during adolescence. The aim of this research is to review literature, articles and research documents that identify adolescent mental health management. The method used in this research is a literature review method where researchers critically examine the ideas contained in the literature for a particular topic. In this study, researchers examined adolescent mental health management. The data used in this research comes from reputable online journal articles published on the internet. The journal search used a database with medium and high quality criteria by entering the keywords Mental Health Management, Adolescent Mental Health Disorders, Trends in Adolescent Mental Health Cases. The articles used were 10 articles published in the last ten years (2015-2024). The results of a review of 10 research sample journals used show that several adolescent mental health management interventions, namely Psychosocial intervention, Mental Health Literacy, Expressive-creative intervention, Psychosocial skills-based interventions, with this intervention can improve adolescent mental health, and can also be preventive against adolescent mental health problems. The choice of methods and media can be adjusted to the targets and goals. Each intervention has its own advantages and disadvantages, and the level of effectiveness varies.